2006
DOI: 10.1159/000097022
|View full text |Cite
|
Sign up to set email alerts
|

IL-13Rα2 Reverses the Effects of IL-13 and IL-4 on Bronchial Reactivity and Acetylcholine-Induced Ca<sup>2+</sup> Signaling

Abstract: Background: The interleukins IL-4 and IL-13 play a key role in the pathophysiology of asthma. The interleukin receptor IL-13Rα2 is believed to act as a decoy receptor, but until now, the functional significance of IL-13Rα2 remains vague. Methods: Bronchial reactivity was quantified in murine lung slices by digital video microscopy and acetylcholine (ACH)-induced Ca2+ signaling was measured in human airway smooth muscle cells (ASMC) using fluorescence microscopy. Results: IL-4 or IL-13 up to 50 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 75 publications
3
28
0
Order By: Relevance
“…Recent studies, however, suggest that IL-13R␣2 may mediate profibrotic responses to IL-13 by an undefined mechanism (35). Expression of IL-13R␣2 can be inducibly regulated on the surface of various cell types including smooth muscle cells (33). Human cell lines overexpressing IL-13R␣2 have reduced signaling responses to IL-13 (64,65), consistent with antagonist function, but there have been relatively few studies of IL-13R␣2 effects on IL-13 responses of primary human cells (33,66,67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, however, suggest that IL-13R␣2 may mediate profibrotic responses to IL-13 by an undefined mechanism (35). Expression of IL-13R␣2 can be inducibly regulated on the surface of various cell types including smooth muscle cells (33). Human cell lines overexpressing IL-13R␣2 have reduced signaling responses to IL-13 (64,65), consistent with antagonist function, but there have been relatively few studies of IL-13R␣2 effects on IL-13 responses of primary human cells (33,66,67).…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 responses are mediated through a receptor consisting of IL-13R␣1/IL-4R␣ chains. An additional binding chain, IL-13R␣2, is inducible on the surface of several cell types, including fibroblasts and smooth muscle cells, and antagonizes IL-13 responses on these cell types (33,34). Recently, however, it has been proposed that, under certain conditions, IL-13R␣2 may act as an agonist, rather than antagonist, of IL-13 responses (35).…”
Section: Induction Of Il-13r␣2 Blocks Hasm Contraction Responsesmentioning
confidence: 99%
“…IL-13Rα2, unlike the type 2 IL-4 receptor (IL-4Rα/IL-13Rα1), does not activate Stat6 signaling, but instead proportionally reduces IL-13 (17,18) and in some cases IL-4 activity (19). Although the function of IL-13 in allergic diseases has been studied extensively, IL-13Rα2 has received much less attention (20,21). IL-13Rα2 was recently shown to control bronchial reactivity following IL-13 stimulation in vitro (21).…”
Section: Introductionmentioning
confidence: 99%
“…Although the function of IL-13 in allergic diseases has been studied extensively, IL-13Rα2 has received much less attention (20,21). IL-13Rα2 was recently shown to control bronchial reactivity following IL-13 stimulation in vitro (21). Nevertheless, the role of the endogenous IL-13Rα2 has not to our knowledge been previously investigated in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Described primarily as a decoy, IL-13Ra2 is a potent antagonist of IL-13 bioactivity mediated through the IL-13Ra1/IL-4Ra complex on human fibroblasts (5)(6)(7)(8), epithelial cells (9)(10)(11), keratinocytes (12,13), and smooth muscle cells (12,14,15). Recent reports suggested that IL-13Ra2 may have some signaling capacity, resulting in fibrotic responses to IL-13 (16).…”
mentioning
confidence: 99%